Overcoming modernity : synchronicity and image-thinking - Yuasa, Yasuo (State University of New York Press, 2008)
"In Overcoming Modernity, which contains the last writings from Yuasa, the prominent Japanese scholar reconsiders the modern Western paradigm of thinking and in its place proposes a more holistic worldview. Through these explorations, engaging a wide range of Western and east Asian thought, Yuasa offers an alternative to the scientific worldview inherited from the seventeenth and eighteenth centuries. This new paradigm involves the integration of space-and-time and mind-and-body, thematics brought together through what Yuasa calls "image-thinking," a mode of thinking that incorporates image-experience."--BOOK JACKET.